Callogenesis and Embryogenic Potential of New Superior Cocoa (Theobroma cacao L.) Genotypes Treated with Ascorbic Acid - Sulistyani Pancaningtyas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Clonal propagation is an alternative method of maintaining the genetic purity of superior cocoa plants (Theobroma cacao L.). The somatic embryogenesis technique is likely the most effective and efficient method for plant propagation. This study aimed at investigating the callogenesis and embryogenic potential of new superior cocoa clones on culture media added with various concentrations of antioxidants and variation in the concentration of auxin hormone combined with ascorbic acid. The superior clones used in this study were MCC 01, MCC 02, Sulawesi 3, ICCRI 07, and ICCRI 09. The parameters observed in this study were percentage of embryogenic callus formation, number of secondary somatic embryos, and percentage of embryo somatic cells that develop into planlets. The addition of 2,4,5-T combined with ascorbic acid affected the initiation of cocoa secondary somatic embryogenesis. Treatment combination of ascorbic acid 100 mg.L-1 and 2,4,5-T 1 mg.L-1 had a significant effect on the initiation of secondary somatic embryogenesis of cocoa in the embryogenic callus phase (4.73%), globular embryos (2.53%), torpedo embryos (4.67%) and sprouts (0.47%). Three clones i.e ICCRI 07, Sulawesi 3 and ICCRI 09 clones showed a higher percentage (3.0%, 2.10%, and 1.80%, respectively) of embryogenic callus growth than the other clones. Meanwhile, on MCC 01 clone, all treatments did not affect the regeneration of embryogenic callus. The combination treatment of organic acid and adenine showed a low embryogenic callus response in MCC 01 and MCC 02 clones. However, MCC 02 clone also did not show a response in form of globular, torpedo, and germination phase somatic embryo regenerations. This indicates that different plant cultivars show different responses to the addition of organic acids. Treatment combinations of adenine 0.0125 mg.L-1 + ascorbic acid 100 mg.L-1 gave the best response to the regeneration of somatic embryos for the globular, torpedo, and g